2019
DOI: 10.1038/s41467-019-11400-9
|View full text |Cite
|
Sign up to set email alerts
|

Circadian control of lung inflammation in influenza infection

Abstract: Influenza is a leading cause of respiratory mortality and morbidity. While inflammation is essential for fighting infection, a balance of anti-viral defense and host tolerance is necessary for recovery. Circadian rhythms have been shown to modulate inflammation. However, the importance of diurnal variability in the timing of influenza infection is not well understood. Here we demonstrate that endogenous rhythms affect survival in influenza infection. Circadian control of influenza infection is mediated by enha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(109 citation statements)
references
References 61 publications
3
106
0
Order By: Relevance
“…Preclinical data show that irrespective of the viral burden, survival following influenza viral infection is determined by the circadian influence on the patterning of the immune response. 25 The circadian gene, Bmal1, is a significant inhibitor of herpes simplex virus (HSV)-1 and influenza viruses, highlighting the role of circadian factors in the regulation of viral infections. 26 As the loss of the circadian rhythm can increase viral replication, viruses can act to sabotage circadian regulation, exemplified by HSV-1 suppression of Bmal1.…”
Section: Circadian Rhythmmentioning
confidence: 99%
“…Preclinical data show that irrespective of the viral burden, survival following influenza viral infection is determined by the circadian influence on the patterning of the immune response. 25 The circadian gene, Bmal1, is a significant inhibitor of herpes simplex virus (HSV)-1 and influenza viruses, highlighting the role of circadian factors in the regulation of viral infections. 26 As the loss of the circadian rhythm can increase viral replication, viruses can act to sabotage circadian regulation, exemplified by HSV-1 suppression of Bmal1.…”
Section: Circadian Rhythmmentioning
confidence: 99%
“…Immune response against L. monocytogenes was induced strongly at ZT8 compared to ZT0, and BMAL1 regulated the circadian changes of the distribution, cytokine production, and bacterial rejection by monocytes. Sengupta et al, showed that BMAL1 regulated the diurnal difference of inflammation against influenza A virus which is induced strongly at the active phase via the monocyte infiltration in lung (62). Next, Fortier et al, found that T cell proliferation after anti-CD3 antibody stimulation became higher at the late rest or the active phase (circadian time (CT) 10-14) in a circadian manner, probably because of oscillating ZAP-70 expression with peak at CT 8 (63).…”
Section: Relationship Between Gcs and Other Circadian Factors On Immumentioning
confidence: 99%
“…Coefficients are adjusted for age, gender, occupation, influenza vaccination status, and general perceived health. a P<0.05. be at increased risk for respiratory infections (29). Two epidemiological studies that examined the relation between shift work and infectious diseases also found an increased incidence of infectious diseases among shift workers (30,31), but one study reported that infectious diseases were more common among non-shift workers (32).…”
Section: Discussionmentioning
confidence: 99%